An updated review on immune checkpoint inhibitor-induced colitis: epidemiology, pathogenesis, treatment strategies, and the role of traditional Chinese medicine - Dong, Huijing; Peng, Yanmei; Wang, Xinmeng; Cui, Huijuan (Frontiers in Immunology, 2025)
Immune checkpoint inhibitor-induced colitis (irColitis) is a common and severe adverse reaction to immune checkpoint inhibitors (ICIs), significantly impacting the treatment outcomes and quality of life of cancer patients. Epidemiological studies indicate that the incidence of irColitis is associated with factors such as the type of ICIs, the patient’s gender, age, and medical history. Although the exact pathophysiology remains unclear, irColitis is thought to be related to immune system activation and dysregulation, gut microbiota imbalance, and impaired epithelial barrier function. This review summarized the epidemiology, clinical presentation, diagnostic criteria, and pathogenesis of irColitis. Additionally, the standard and novel therapeutic strategies of irColitis, including corticosteroids, biologics, and gut microbiota interventions, more importantly the potential and application of Traditional Chinese Medicine (TCM). Future researches call for deeper mechanistic investigations, the development of biomarkers, and reveal the integration of TCM therapies within individual immunotherapy frameworks.